TARAF HIDUP BURUH TANI KELAPA SAWIT DI DESA LIBO JAYA KECAMATAN KANDIS KABUPATEN SIAK - Wardani, Eti; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Writer do the research entitling "level live the farmworker of coconut sawit in countryside libo jaya of subdistrict of kandis of regency siak" This Research aim to to analyse: (1) level live the farmworker of kelapa sawit,(2) social relation of farmworker with the farmer of farm owner, (3) adaptation strategy which in conducting farmworker at a period of difficult. Research planning in countryside Libo jaya of Subdistrict of Kandis of Regency Siak mostly its society work as farmworker of coconut sawit with the farmworker amount increasing every year. Sum the responder at this research as much 72 responder. Method using in this research is descriptive quantitative. Result of research indicate that: (1) Level live the farmworker of coconut sawit in Countryside Libo jaya of Subdistrict of Kandis of Regency Siak be at the prosperity storey level that is secure and prosperous family of 1, where besides them able to fulfill the its base requirement, They also start to pay attention to the its childs education and economically own the equipments terknologi personally like tv, motorbike and others. (2) social relation farmworker of coconut sawit with the farmer of farm owner have been intertwined by pattern of job relation which is requiring each other and is profiting each other that is structural co-operative relation. ( 3) adaptation strategy done by farmworker of a period of difficult is active strategy, that is exploiting of house composition and all labour wife which follow to work. Besides active strategy, network strategy is also done by farmworker. Because them of a more regular borrow to owner farmer of at a period of difficult.Keyword: Prosperity, Social Relation, Adaptation Strategy